Compliance and knowledge of health professionals regarding airborne precautions - Hélio Galdino Júnior; Moníque Lopes de Souza; Luzinéia Vieira dos Santos; Anaclara Ferreira Veiga Tipple (Rev Rene)
Objective: to assess compliance to measures regarding airborne precautions, as well as knowledge about the application of these measures among health professionals of a service specialized in the care of patients with tuberculosis. Methods: an observational cross-sectional study, which evaluated compliance opportunities through observation (n=143) and knowledge through a questionnaire (76). Results: the door of the isolation areas remained open at 13.3%. The wards had high filtration filter, but in 60.9% of observations this was off. As for the mask, 99.3% of health professionals used it before entering the isolation area and 58.7% kept the same mask after leaving. Responses from professionals about airborne precautions characterized little knowledge about these measures. Conclusion: continuing education campaigns to raise awareness can be adopted to increase the compliance to airborne precautions and reduce the risk of occupational exposure.